2010
DOI: 10.1002/ejoc.201001055
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Alkylation of Indoles with Tertiary Propargylic Alcohols: Scope and Limitations

Abstract: The direct alkylation of indoles with a wide variety of tertiary propargylic alcohols under Brønsted acid catalysis has been studied. A general and environmentally friendly method for the synthesis of C3-propargylated indoles with a quaternary carbon at the propargylic position has been developed. The reactions are highly regioselective regarding both the indole and the alkynol counterparts.Only with N-unsubstituted-2-arylindoles a competitive S N´ reaction takes place affording 3-dienyl or 3-allenylindoles de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 105 publications
0
24
0
Order By: Relevance
“…These derivatives were easily accessible from simple and commercially available N-methyl indole, carbonyl and alkyne compounds applying our previously developed Brønsted acid-catalyzed direct substitution of propargylic alcohols (Scheme 2a). 45,50,51 Then, using Myers conditions, 52 i.e., the addition of alkynol 4 to a mixture of PPh 3 and DIAD (diisopropyl azodicarboxylate), followed by the addition of NBSH (o-nitrobenzenesulfonylhydrazide), 53 allene derivatives 1a-i were obtained in good yields (Scheme 2b). On the other hand, benzyl-functionalized acetylenes 5 were efficiently transformed in the corresponding allenes 1j-m by base promoted isomerization using KOH 54 or t-BuLi (Scheme 2c).…”
Section: Resultsmentioning
confidence: 99%
“…These derivatives were easily accessible from simple and commercially available N-methyl indole, carbonyl and alkyne compounds applying our previously developed Brønsted acid-catalyzed direct substitution of propargylic alcohols (Scheme 2a). 45,50,51 Then, using Myers conditions, 52 i.e., the addition of alkynol 4 to a mixture of PPh 3 and DIAD (diisopropyl azodicarboxylate), followed by the addition of NBSH (o-nitrobenzenesulfonylhydrazide), 53 allene derivatives 1a-i were obtained in good yields (Scheme 2b). On the other hand, benzyl-functionalized acetylenes 5 were efficiently transformed in the corresponding allenes 1j-m by base promoted isomerization using KOH 54 or t-BuLi (Scheme 2c).…”
Section: Resultsmentioning
confidence: 99%
“…At this point, and taking advantage from our developed methodology for the direct propargylation of indoles under Brønsted acid catalysis, [5] we envisaged that this new process could be performed in a straightforward manner from simple indoles 3 and but-2-yne-1,4-diols 4 with the loss of water as the only by-product (Scheme 4). The required acetylenic 1,4-diols 4 are easily prepared whereas few but highly interesting synthetic application have been described for them in recent years [17] including a remarkable acid-catalyzed domino reaction of highly activated tetraarylbut-2-yne-1,4-diols with 1-naphthol.…”
Section: Methodsmentioning
confidence: 99%
“…[4] In this context, we have described a robust method for the reaction of indoles with propargylic alcohols that provides a suitable access to a wide variety of 3-propargylindole derivatives (Scheme 1). [5] In addition, cascade rearrangements of propargylic alcohols, and their derivatives, have been demonstrated to be a useful synthetic tool [6] via their transformation into allenic carbocations [7] and subsequent intramolecular trapping with electron-rich arenes, alkenes, enols, and heteroatom nucleophiles. [8] At this point we thought about the possibility that a Brønsted acid could trigger an intramolecular nucleophilic attack of the indole onto a propargylic cation, generated from the corresponding alcohol, followed by the opening of the cyclopropyl ring, thus mimicking the behaviour of cationic gold(I) catalysts (Scheme 1), as it has been reported that some reactions can be catalyzed by -acids as well as by protons.…”
mentioning
confidence: 99%
“…14 Later, Sanz's group performed a direct alkylation reaction between indoles and tertiary propargylic alcohols catalysed by p-toluenesulfonic acid (PTSA, 5 mol%), in MeCN, at room temperature. 15 Alkylation of furans by benzyl and propargyl alcohols 14,16 in the presence of Brønsted acids as catalyst have attracted the interest of the researchers 17 and selected results are shown in Table 5. Furthermore, the catalytic nucleophilic substitution of tertiary alcohols 11,18,19 using carbon-or heteroatombased nucleophiles in the presence of Brønsted acid has been reviewed 20 and selected results are shown in Table 6.…”
mentioning
confidence: 99%